A escada invisível: aspectos sociais, políticos e econômicos do negro no mercado de trabalho 2002 a 2014 - Oliveira, Paulo Adriano Guedes de (2016)
The objective of this work is to perform an of social aspects analysis, political and economic of black people in the Brazilian labor market between the years 2002 to 2014. To assist in the analysis, data will be presented collected between the years in question to give support to work. There is a latent socioeconomic gap in Brazilian society between whites and blacks, this situation leads to numerous social, political and economic problems for the black population. The same holds the worst indicators and sanitation rates, health, education, employment, income, among others. Therefore, analyze the racial question via the labor market, it is something entirely valid, since it is that part of the socio-economic relations take place. Not counting that is through the labor market that people can generate income so they can get their personal development